1991
DOI: 10.1016/0020-7373(91)90037-8
|View full text |Cite
|
Sign up to set email alerts
|

High precision touchscreens: design strategies and comparisons with a mouse

Abstract: Three studies were conducted comparing speed of performance, error rates, and user preference ratings for three selection devices. The devices tested were a touchscreen, a touchscreen with stabilization (stabilization software filters and smooths raw data from hardware), and a mouse. The task was the selection of rectangular targets 1, 4, 16, and 32 pixels per side (0.4x0.6, 1.7x2.2, 6.9x9.0, 13.8x17.9 mm respectively). Touchscreen users were able to point at single pixel targets, thereby countering widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
2
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 9 publications
9
172
2
2
Order By: Relevance
“…Second, we used a vision-based input technology which is more sensitive to touches and capable of detecting non-finger contacts, too. In specific, we observed that lifting the finger off the surface sometimes caused the selected target to move as described by Sears et al [23]. Therefore, it was not properly aligned with the dock anymore which was counted as dragging error.…”
Section: Differences In Pointing and Draggingmentioning
confidence: 75%
See 1 more Smart Citation
“…Second, we used a vision-based input technology which is more sensitive to touches and capable of detecting non-finger contacts, too. In specific, we observed that lifting the finger off the surface sometimes caused the selected target to move as described by Sears et al [23]. Therefore, it was not properly aligned with the dock anymore which was counted as dragging error.…”
Section: Differences In Pointing and Draggingmentioning
confidence: 75%
“…(b) Indirect multi-touch: separate output with display of hand contours (a) Direct multi-touch: input and output space coincide Direct versus indirect input has been studied widely for single-pointer interaction, comparing indirect input devices with direct-touch or pen input (e.g., [20,23]). A recent study is close to ours in spirit, as it focuses on a single in-put technology, here a stylus pen, which is compared for direct and indirect interaction showing that indirect use can perform as well for certain tasks [8].…”
Section: Related Workmentioning
confidence: 99%
“…Prior finger-based pointing techniques suffered from two problems, which Shift remedies: the occlusion caused by the hand, and the lack of precision caused by fingers that are larger than many targets. Prior to Shift, the Offset Cursor was a popular design that placed the selection point a standard distance above the finger contact point (Potter et al, 1988;Sears and Shneiderman, 1991). But the Offset Cursor required users to ''aim low'' in anticipation of the constant offset, ruining the possibility of direct-touch for large targets.…”
Section: Thumb-and Finger-based Mobile Device Interactionmentioning
confidence: 99%
“…In order to isolate the physical performance of hand postures on a mobile device, we had to create an experiment apparatus that circumvented the two wellknown perceptual problems of direct-touch on touch screens, namely the occlusion caused by the user's hand and the unwieldy ''fat finger'' that creates an uncertain touch location (Potter et al, 1988;Sears and Shneiderman, 1991;Vogel and Baudisch, 2007;Wigdor et al, 2007). We argue that innovations in display and sensing technologies will continue to ameliorate these problems, and therefore they should not confound our results.…”
Section: Apparatusmentioning
confidence: 99%
“…Applicable comparative studies on the candidate devices were reviewed (Albert, 1982;Helander, 1988;Karat, et al, 1986;Sears, Shneiderman, 1991) and user feedback was solicited. Prototype mouse and trackball interfaces have been developed with the Supervisor Display.…”
Section: Input Devicesmentioning
confidence: 99%